1998
DOI: 10.1055/s-2006-957469
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Unusual Lupane Saponins fromBupleurum fruticescens

Abstract: Extracts from Bupleurum fruticescens were examined for oral and topical anti-inflammatory activities. The BuOH extract proved to be active against carrageenan and tetradecanoylphorbol acetate acute edemas and allowed the isolation of three saponins identified by spectroscopic techniques as 3 beta-O-(O-alpha-L-rhamnopyranosyl-(1-->4)-O-[beta-D-glucopyranosyl- (1-->6)]-O-beta-D-glucopyranosyl)lup-20(29)-ene-23,28-dioic acid (fruticesaponin A), 3 beta-O-(O-alpha-L-rhamnopyranosyl-(1-->4)-O-beta-D-glucopyranosyl) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
148
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(153 citation statements)
references
References 2 publications
3
148
0
2
Order By: Relevance
“…These compounds are biologically active and exhibit diversified activities. Just et al (1998) reported the inhibitory effect of saponins on inflamed cells and this has supported the usefulness of this plant in managing inflammation. Saponins cause the leakage of proteins and degradation of cell wall enzymes (Zablotowicz et al, 1996).…”
Section: Discussionmentioning
confidence: 70%
“…These compounds are biologically active and exhibit diversified activities. Just et al (1998) reported the inhibitory effect of saponins on inflamed cells and this has supported the usefulness of this plant in managing inflammation. Saponins cause the leakage of proteins and degradation of cell wall enzymes (Zablotowicz et al, 1996).…”
Section: Discussionmentioning
confidence: 70%
“…In the first phase (0-1 h after injection of carrageenan) histamine, bradykinin, and serotonin are involved (Crunkhorn & Meacock, 1971;Vinegar et al, 1969), while the second phase (after 1 h) is attributed to infiltration of leucocytes, production of oxygen-derived free radicals and release of prostaglandins, protease, and lysosome (Di et al, 1971;Halici et al, 2007;Vircheva et al, 2011). The ethanol extract of N. officinale exhibited prominent protective effects on the development of paw swelling by carrageenan over a period of 4 h. This finding indicates the inhibitory effects of N. officinale against release of the pro-inflammatory mediators involved in the two phases of the carageenan test (Just et al, 1998). Our pathological examination confirmed that the watercress extract reduced edema the migration of leucocytes into carrageenan-treated paws.…”
Section: Discussionmentioning
confidence: 99%
“…Lignans strongly suppressed the incorporation of [ Saponins are steroid or triterpenoid glycosides which derive their name from their ability to form stable, soap-like foams in aqueous solutions and several biological effects which include immunostimulant and antitumourigenic properties [17]. Saponins have also been shown to be anti-inflammatory [18]. In the present study, TLC and staining with anisyl aldehyde in sulfuric acid was used to ascertain its presence.…”
Section: Discussionmentioning
confidence: 90%